2023
DOI: 10.1186/s43161-023-00133-y
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and utilization of standardized stroke outcome measures among physiotherapists in tertiary health institutions in Anambra State, Nigeria

Abstract: Background Knowledge and utilization of standardized stroke outcome measures (SOMs) are important as it helps in the evaluation of patient response to therapy and decision of further step in patient care. This study evaluated the current knowledge and utilization of standardized stroke outcome measures and the factors that influence them. Methods A cross-sectional survey research design was used for the study. The consecutive sampling technique was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…Female PTs were more likely to use SOMs compared to males. These findings have been shared and refuted by some previous studies 16 , 23 - 26 . Okonkwo et al 23 consistently showed that female PTs had better utilisation.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Female PTs were more likely to use SOMs compared to males. These findings have been shared and refuted by some previous studies 16 , 23 - 26 . Okonkwo et al 23 consistently showed that female PTs had better utilisation.…”
Section: Discussionsupporting
confidence: 72%
“…These findings have been shared and refuted by some previous studies 16 , 23 - 26 . Okonkwo et al 23 consistently showed that female PTs had better utilisation. However, Al-Muqiren et al 15 showed that gender had no relationship with SOMs utilisation.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation